2017
DOI: 10.1007/s00586-017-5033-7
|View full text |Cite|
|
Sign up to set email alerts
|

Spinopelvic parameter changes and low back pain improvement due to femoral neck anteversion in patients with severe unilateral primary hip osteoarthritis undergoing total hip replacement

Abstract: Patients with concomitant unilateral HOA and LBP showed a marked anteverted FNA in the arthritic hip and a spinopelvic misalignment. After THR, a relief of both hip and low back pain and a change in spinopelvic parameters is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 32 publications
0
63
0
1
Order By: Relevance
“…In a prospective study, Weng reported a signi cantly larger SS and smaller PT in patients with hip OA [6]. Piazzolla reported that patients with hip OA and low back pain have signi cantly increased SS, LL, and forward inclination of the trunk [17]. Yoshimoto chose individuals with low back pain as controls and reported that patients with hip OA showed signi cantly higher PI, SS and LL [7].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Weng reported a signi cantly larger SS and smaller PT in patients with hip OA [6]. Piazzolla reported that patients with hip OA and low back pain have signi cantly increased SS, LL, and forward inclination of the trunk [17]. Yoshimoto chose individuals with low back pain as controls and reported that patients with hip OA showed signi cantly higher PI, SS and LL [7].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we evaluated the surgical history of joints but not the joint lesions and lower extremity alignment. Several studies indicated that hip lesion and leg length alignment had played an important role in the occurrence of LBP in non-RA patients [35][36][37]. RA affects all synovial joints, causing painful swelling that can cause bone erosion, joint deformity, and malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study in which the comparison group consisted of normal controls, Weng et al reported a significantly larger SS, smaller PT, and comparable LL and PI in patients with hip OA [9]. Piazzolla et al [18]reported that patients with unilateral hip OA and low back pain have significantly increased SS, LL, and forward inclination of the trunk. In addition, the authors also found increased femoral neck anteversion in the arthritic hip when compared to the contralateral healthy hip.…”
Section: Discussionmentioning
confidence: 99%
“…Parvizi et al [24] reported that 49% of patients with end-stage hip arthritis had LBP. In a study of 91 primary hip OA patients who underwent THA, Piazzolla [18] Pelvic tilt has been and remains a concern for hip surgeons because anterior or posterior pelvic tilt has a substantial impact on the orientation of the acetabular cup. For every 1°of posterior pelvic tilt, there is a corresponding increase of 0.7°-0.8° of acetabular anteversion [6,25,26].…”
Section: Discussionmentioning
confidence: 99%